Predictive model of students’ continuance intention in massive open online course among university students - Aminu, Daneji Aisha (2017)
Rapid development of digital technologies creates innovative ways of learning known as Massive Open Online Course (MOOC) which has been introduced at most universities. However, previous study have shown that low course completion rate and limited amount of studies to examine factors that influence students’ continuance intention towards using MOOC. Therefore, the main purpose of this study is to predict factors that influence students’ continuance intention towards using MOOC among university students based on Expectation-Confirmation model and Technology Acceptance Model. By means of reviewing the related literature, factors namely perceived usefulness, perceived ease of use, expectation-confirmation, satisfaction and MOOC continuance intention were examined. This study implemented a survey research design. The instrument used was an online questionnaire. To measure the reliability of the instrument, a pilot study was conducted prior to the actual study towards 32 UPM students whereby a Cronbach alpha values ranged from .738 to .821 was obtained. The actual study was conducted on a sample of 368 undergraduate students. The data was analyzed descriptively using SPSS 22 and Analysis of Moment Structures (AMOS) 2I. The outcome of testing the model revealed that among the nine paths of the structural model, seven paths were significant and two were not. The paths that reflected significant effects were as follows: (1) students’ perceived ease of use have effects perceived usefulness of MOOC (β=. 481, p<. 001); (2) students’ expectation confirmation have effect on perceived usefulness (β=. 367, p<. 005); (3) students’ expectation-confirmation have effect perceived ease of use of MOOC (β=. 918, p<. 001); (4) perceived usefulness have effect on MOOC continuance intention (β=. 374, p<. 001); (5) students’ expectation-confirmation have effect on satisfaction with MOOC (β=.800. p<.001); (6) students’ perceived ease of use of MOOC have effect MOOC continuance intention (β=-.310, p<.001); (7) students’ satisfaction have effect on MOOC continuance intention (β=.840, p<.001). Besides, the paths with non-significant effects were: students’ perceived usefulness does not have effect on satisfaction with MOOC (β=. 058, p>.05); students’ perceived ease of use does not have effect on satisfaction with MOOC (β=. 074, p>.05). The empirical results of the study indicates that perceived usefulness, perceived ease of use and satisfaction with the use of MOOC are strong predictors of MOOC continuance intention. The overall structural model with nine paths has explained 79.4% percent of the variance for putra MOOC continuance intention among public university students.